Clinical profile of patients submitted to coronary artery bypass graft surgery and valve replacement in a tertiary hospital of Southern Braz - Mello, Mariana Brondani de (2019)
Objective: To analyze the clinical profile of the patients submitted to coronary artery bypass graft (CABG) and valve replacement (VT) at a tertiary hospital in the southern region of Brazil. Methods: Cross-sectional and retrospective study with data collection obtained from the registry of patients submitted to cardiac surgery from April 2016 to March 2017 in the Hospital Universitário de Santa Maria (HUSM). The normality of the variables was evaluated by the Shapiro-Wilk test. Prevalence data were presented in absolute frequencies and percentages. In order to verify the correlation between risk factors and length of hospital stay in the intensive cardiology unit (ICU) as well as between risk factors and postoperative complications (PO), the Pearson correlation coefficient was used and the significance level was set at p<0.05 for all analyses. Results: The sample consisted of 44 patients, with average age of 62.31 ± 10.85 years, of which 28 (64%) were male. The most frequent procedure was CABG in 28 patients (64%), followed by valve replacement in 9 (20%) and concomitant CABG and valve replacement in 7 (16%). The most prevalent risk factors observed in these patients were diabetes mellitus (DM) (82%), systemic arterial hypertension (SAH) (82%) and previous history of smoking (36%). The average extracorporeal circulation time (ECC) was 102.88 ± 38.11 minutes and total surgery time was 276.7 ± 82.86 minutes. There was no significant correlation between risk factors and length of hospital stay in the ICU (r = 0,125, p = 0,416) and between risk factors and complications in the PO (r = 0,041, p = 0,791).Conclusion: The majority of the patients in this study were male, and a significant prevalence of comorbidities such as SAH and DM was observed. These findings may reveal a more serious condition to increase the risk of cardiovascular diseases.